2011
DOI: 10.2172/1076794
|View full text |Cite
|
Sign up to set email alerts
|

The Magellan Final Report on Cloud Computing

Abstract: Executive SummaryThe goal of Magellan, a project funded through the U.S. Department of Energy (DOE) Office of Advanced Scientific Computing Research (ASCR), was to investigate the potential role of cloud computing in addressing the computing needs for the DOE Office of Science (SC), particularly related to serving the needs of midrange computing and future data-intensive computing workloads. A set of research questions was formed to probe various aspects of cloud computing from performance, usability, and cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Cloud computing is desirable for broad community access, for having a common platform where model results can be intercompared, and for dealing with surges in demand that may overwhelm local systems. Cloud computing has been able to outperform local supercomputers for a low number of cores (e.g., Montes et al, 2020), but HPC applications with intensive internode communication have previously not scaled well to a large cluster on the cloud (Mehrotra et al, 2016;Coghlan and Katherine, 2011). Zhuang et al (2020) deployed GCHP on the AWS cloud for easy user access and demonstrated efficient scalability with performance comparable to the NASA Pleiades supercomputer.…”
Section: Cloud Capabilitymentioning
confidence: 99%
“…Cloud computing is desirable for broad community access, for having a common platform where model results can be intercompared, and for dealing with surges in demand that may overwhelm local systems. Cloud computing has been able to outperform local supercomputers for a low number of cores (e.g., Montes et al, 2020), but HPC applications with intensive internode communication have previously not scaled well to a large cluster on the cloud (Mehrotra et al, 2016;Coghlan and Katherine, 2011). Zhuang et al (2020) deployed GCHP on the AWS cloud for easy user access and demonstrated efficient scalability with performance comparable to the NASA Pleiades supercomputer.…”
Section: Cloud Capabilitymentioning
confidence: 99%